Baroreflex sensitivity and responses to the Valsalva manoeuvre in subjects with diabetes mellitus. Issue 2 (February 1976) - Bennett, T; Hosking, D J; Hampton, J R
Abstract : Baroreflex sensitivity was measured in a group of diabetic patients from the slope of the regression of pulse interval on systolic arterial pressure, during elevation of pressure induced by phenylephrine. The response to Valsalva's manoeuvre was assessed in the same subjects. There was a good correlation between the two tests in the identification of patients with a parasympathetic autonomic disturbance, but measurements of baroreflex sensitivity were more readily quantifiable than were the responses to Valsalva's manoeuvre. Furthermore, baroreflex sensitivity could be measured in patients with sympathetic nervous dysfunction in whom vagal function could not be assessed by means of the Valsalva manoeuvre. Measurement of baroreflex sensitivity is likely to be suitable for longitudinal studies of the progress of diabetic autonomic neuropathy.